The effectiveness of promotional tools to create customer awareness / Mohd Amirza Misnadi - Misnadi, Mohd Amirza (Faculty of Business and Management, 2006)
In this modern day business environment, the business world is getting more competitive and aggressive by the day. Businesses compete with each other in order to boost sales by trying to come up with the best advertisement and promotion by using all tools available. Promotion is the basic prominent in making sure each local firm penetrate market and keep sustaining growth for existing market. However, JKiNG Sdn Bhd which has limited resources, those promotions cannot be done in full swing by firms; hence the objectives of promotions cannot be achieved or targeted. This study provided the readers about the research done among consumer around Johor Bahru. The main purpose of this study is to identify the effectiveness promotional tools to create customer awareness. The objectives of this study are to determine the effectiveness of the existing promotion tools used by JKiNG Sdn Bhd and to study the customer awareness towards promotional activities done by JKiNG Sdn Bhd. In this research random sampling will be used, which is under the non-probability sampling. The sample size is 50 respondents; there are selected respondents of JKiNG customer around Johor Bahru area. From finding, researcher found that the effective existing promotional tool to create customer awareness is advertisement and the effective promotional tool to create customer awareness and customer expected information must be clear in their promotion tools.